Evaluation of shooting sports achievement development program at PB PERBAKIN - Tiana Wanda Ariesta; Ramdan Pelana; Yasep Setiakarnawijaya (Gladi : Jurnal Ilmu Keolahragaan, 2022)
The purpose of research is evaluation of the implementation of the national sports achievement development program for shooting sports in PB PERBAKIN using the CIPP evaluation model (Contexs, Input, Process, Product). The sampling technique was purposive sampling, so the sample in this study is 39 people. Collecting data using observation, interviews, questionnaires, and documentation. The data analysis technique used in this research is quantitative and qualitative descriptive analysis. The results showed that the overall results of the evaluation of the coaching program for improving national sports achievement in the airsoft sport in PB. PERBAKIN has been running well with a score of 67,92. In terms of context, it has gone well with a nikai of 69,40. In terms of input it has been going well with a value of 70,21. In terms of the process has been going well with a value of 67,35. In terms of the product, in general, the achievements achieved are quite good, but the achievement is not maximized so that a score of 56,75 is obtained even though it is not in line with expectations but in this evaluation there are good things, namely the support and enthusiasm of parents for athletes is very good.